Turkey and the EU: Politics and Economics of Accession - Harry Flam (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper discusses political and economic aspects of Turkish accession. Under present rules, Turkey would have the greatest number of council votes within twenty years, and receive the largest budget transfer. Free migration may increase the Turkish immigrant population in Germany from 2 to 3.5 million in thirty years. Most of the economic effects will be felt by Turkey, particularly in agriculture. The main obstacles to accession are not economic, but political. Historical experience prevents Turkey from eliminating the decisive political role of the military, giving Kurds and other minorities cultural rights and upholding basic human rights.
Keywords: 330; Turkey